Analysis of representations of nature of Science and indigenous knowledge systems in South African Grade 9 Natural Science textbooks - Moloto, Matlhodi Francina (My University, 2012)
This study analyzed representations of Nature of Science (NOS) and Indigenous Knowledge Systems (IKS) in three South Africa Grade 9 Natural Science textbooks. The textbooks were purposefully selected from a possibility of ten textbooks available on the public market and used in science classrooms in the Gauteng Province of South Africa. The aim of the analysis was to determine the extent to which both NOS and IKS were represented and to ascertain whether the representations were: naïve or informed; and implicit or explicit. The content analysis of the textbooks was based on adaptations of analytical frameworks developed by Akerson, Abd-El-Khalick and Lederman (2000) for NOS and Ninnes (2000) for IKS, respectively. For NOS the analysis focused on seven tenets, which are; science is empirical, the difference between observation and inference, functions and relations between theories and laws, the role of creativity and imagination in science, the tentativeness of scientific knowledge, the social and cultural embeddedness of the scientific process, and subjectivity of science. The analysis for IKS representations focused on four pillars of IKS which are; indigenous legends and myths, indigenous technology, indigenous knowledge of the natural world, and indigenous social life. It was found that, for the NOS, in all the three textbooks, only the empirical nature of science and observation and inference are represented to a considerable extent and mainly in a naïve and implicit manner. The other investigated tenets are either minimally represented or not represented at all. Representations of IKS in the three textbooks were also found to be very minimal and mainly naïve and implicit. It is concluded the selected science textbooks do not respond well to the NCS mandate of integrating NOS and IKS into mainstream science education. Recommendations for improving integration of NOS and IKS into the school science curriculum are suggested for textbooks authors, curriculum developers and science educators. Key words nature of science, indigenous knowledge systems, textbooks, natural science, naive, informed, implicit, explicit, positivism, constructivism
Keywords: Natural science - Study and teaching (Secondary) - South Africa.; Science - Study and teaching - South Africa.; Indigenous knowledge systems.